Analysis of Cybersecurity Awareness and Behavior Among Students of IPB University: An Integration of Protection Motivation Theory and Theory of Planned Behavior - Muhammad Gustara; Eko Ruddy Cahyadi; Bagus Sartono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the factors influencing cybersecurity awareness and behavior among students of IPB University by integrating the Protection Motivation Theory (PMT) and the Theory of Planned Behavior (TPB). Data were collected through an online survey involving 255 students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that behavioral intention and awareness significantly influence cybersecurity behavior. Variables such as attitude, subjective norms, response efficacy, and perceived severity contribute significantly to shaping intention and awareness, whereas perceived vulnerability and self-efficacy do not directly affect intention. These results reinforce the validity of integrating PMT and TPB in explaining cybersecurity behavior determinants and offer practical implications for developing evidence-based cybersecurity literacy programs in academic settings.